Implementasi Sistem Informasi Aplikasi Nota Dinas Elektronik dalam Pengelolaan Surat di JLI Jakarta - Ria Aprianti; Sri Astuti (Jurnal Utilitas, 2019)
This study aims to determine the activities of Input, Process, Output, and Feedback from the Electronic Office Note Application. The study uses descriptive qualitative methods. The data source is chosen by Purposive Sampling with criteria to master or understand and is classified as a User of Electronic Service Memorandum Application (NDE). Data collection techniques using participatory observation, structured interviews and documentation. The results of research conducted at Jasamarga Learning Institute on the Application of Electronic Service Notes (NDE) in the Management of Incoming and Outgoing Letters. (1) Inputs from Electronic Service Note (NDE) applications, namely Documents (2) Process of Electronic Service Note Applications (NDE), namely Sorting, Letter Disposition, Letter handing activities/letter distribution, Letter recording, Storage, making outgoing letters, numbering and recording of outgoing letters and sending outgoing mail (3) Outputs from the Electronic Service Note (NDE) Application, Speeding up the rediscovery, and Effective and Efficient (4) Feedback from the Electronic Service Note (NDE) Application, namely Users, Program Evaluation, Program Policies.